Malignant transformation of sinonasal inverted papilloma - Farhat dr (Fakultas Kedokteran USU, 2013)
Inverted papilloma is a benign epithelial growth in the underlying stroma of the nasal cavity and paranasal sinuses that is best known for its invasiveness, tendency to recur and association with malignancy.The most common presenting symptom is nasal obstruction. CT is the techniques of choice for pretreatment staging of neoplasms of the sinonasal tract. Complete surgical extirpation is the aim of treatment of choice for these tumor. A 66 years old man was admitted to ENT-HNS Department with main complaint mass in his left nasal cavity since 3 years and 7 months ago. In the beginning, mass as big as corn arised in his left nasal cavity. The mass enlarged in 7 months full fill left nasal cavity. Sinus paranasal CT Scan showed tumor of left nasal cavity extend to left maxillary sinus, left posterior ethmoidalis sinus and left frontalis sinusitis. He was underwent tumor extirpated with midfacial degloving on May 2008. Histopatology examination from biopsy and operation were inverted papilloma. Mass on left nasal cavity raised again 2 years and 8 months after operation. On examination, anterior rhinoscopy showed pinkish mass with ulceration full fill the left nasal cavity. Sinus paranasal CT Scan showed tumor of left nasal cavity extend to left maxillary sinus, left posterior ethmoidalis sinus and left frontalis sinusitis. Histopatology examination from biopsy was inverted papilloma. The tumor was extirpated with lateral rhinotomy. Histopatology examination was carsinoma cell squamous.We diagnosed the patient with sinonasal carcinoma.Keywords : inverted papiioma; sinonasal; malignant transformation